Laminated Veneer Lumber-Journey So Far - Prakash, V.; Singh, M. P.; Sujatha, D.; Uday, D. N.; Mamatha, B. S.; Kiran, M. C.; Murthy, Narasimha; Ramkumar, V. R. (Indian Forester, 2025)
Laminated veneer lumber (LVL) is a wood composite which can be produced from a variety of fast - growing short rotation plantation timbers species and is considered as best substitute for traditional timbers intended to be used for structural applications. LVL has the potential to cater increasing demands of construction industry. The research that has been carried out so far with respect to manufacturing, types of LVL, timber species and adhesives used for manufacturing LVL, methods of enhancing its strength properties, applications and embodied energy associated with it in comparison to other materials viz. steel, aluminium etc. which are used for similar purposes is reviewed in this paper. The review suggests that LVLs can be manufactured from a wide range of short rotation plantation timber species grown dominantly in various geographical locations using suitable adhesives which plays a vital role in imparting strength to the panel. Enhanced strength properties of LVL can be obtained by incorporating suitable reinforcements within and external to the laminate. Wood being the main raw material for manufacturing LVL, it stores more carbon than emitted during its production, also the embodied energy associated with LVL is less compared to other building materials used for similar applications and hence it can be considered as a green building material. Being the best alternate to the conventional timber LVLs provide ample opportunity for low grade plantation timbers to be utilized for applications such as furniture frame work, windows and door frames.